Watch and wait strategies for rectal cancer: A systematic review - In Ja Park (Precision and Future Medicine, 2022)
Watch and wait (WW) strategies have been suggested for patients with clinical complete regression (cCR). The WW approach was first introduced by Habr–Gama in patients with cCR after neoadjuvant treatment. Actually, it is not “no surgery” but “deferral of surgery;” therefore, the WW approach or non-operative management is a representative term currently. The number of publications regarding WW for rectal cancer has increased abruptly. We conducted a systematic review of PubMed for literature published on WW. It is now one of the most interesting issues in rectal cancer treatment. Many studies have reported comparable overall survival with WW and radical resection. However, a high local regrowth rate is a problem, and proper salvage management is the main concern in the WW approach. Adequate patient selection is necessary to achieve favorable oncologic outcomes. However, the appropriate definition and diagnostic method for cCR have not yet been clearly defined. Indeed, advances in local control have not translated into overall survival improvement, and many efforts have been made to improve distant metastasis control and overall survival and improve clinical response to preoperative chemoradiotherapy. In this review, oncologic outcomes, ongoing efforts to improve oncologic outcomes, and limitations for clinical practice were evaluated and described.